The making of an ecologist: my career in Alaska wildlife management and conservation - Klein, David R., author; Brewster, Karen, editor; University of Alaska Press, publisher (Colorado State University. Libraries, 2019)
This is an innovative and collaborative life history of one of Alaska's pioneering wildlife biologists. David R. Klein has been a leader in promoting habitat studies across wildlife research in Alaska, and this is his first-hand account of how science and biological fieldwork has been carried out in Alaska in the last sixty years. This book tells the stories of how Klein did his science and the inspiration behind the research, while exposing the thinking that underlies particular scientific theories. In addition, this book shows the evolution of Alaska's wildlife management regimes from territorial days to statehood to the era of big oil. The first portion of the book is comprised of stories from Klein's life collected during oral history interviews, while the latter section contains essays written by Klein about philosophical topics of importance to him, such as eco-philosophy, the definition of wilderness, and the morality of hunting. Many of Klein's graduate students have gone on to become successful wildlife managers themselves, in Alaska and around the globe. Through The Making of an Ecologist, Klein's outlook, philosophy, and approach toward sustainability, wildlife management, and conservation can now inspire even more readers to ensure the survival of our fragile planet in an ever-changing global society.
Early influences -- A childhood outdoors during turbulent times -- Time in the woods -- Discovering Alaska, discovering self -- Entrée into ecological fieldwork -- Falling in love with the Alpine -- Deer ecology and management in southeast rainforests -- Research -- The St. Matthew Islands: challenging conventional ecological wisdom -- Leading the Alaska cooperative wildlife research unit and mentoring graduate students -- Wildlife reactions to oil development -- Ungulate research across the circum-arctic -- Soviet-U.S. détente exchanges in arctic ecology -- Expanding horizons beyond the Arctic -- Managing wildlife in Alaska: territorial days, statehood, and the era of big oil -- Not quite retired: staying connected to science -- The human perspective -- Walking in the footsteps of Aldo Leopold: a scientific legacy -- Ethical considerations in caribou management -- Valuing northern lands -- Defining the wilderness concept -- Environmental philosophy: people and the environment -- Hunting ethics and the morality of hunting -- On being objective -- Alaska's people, economics, and resources.
Keywords: Wildlife management -- Alaska; Ecologists -- Alaska -- Biography; Wildlife conservation -- Alaska; Klein, David R.; Natural history -- Alaska; Alaska -- Environmental conditions